Torna-se cego : liminaridade, aprendizagem e subjetividade entre pessoas com deficiência visual em Cuiabá/MT - Yamamura, Leonardo Bueno (2020)
This research was based on an ethnographic study with people with visual impairments in Cuiabá-MT between the years 2017 and 2019. The contexts contemplated were the State Public Library Estevão de Mendonça, the Instituto de Cegos do Estado de Mato Grosso (Icemat) and the Centro de Apoio e Suporte à Inclusão da Educação Especial (Casies). From the first concerns felt in the field, we tried to think about the difference between “losing sight” and “becoming blind”. As a result of this cultural and symbolic phenomenon, I deepen the analysis in two theoretical-conceptual approaches: learning and subjectivity. With this objective, the present debates were used: a) the rituals of passage (VAN GENNEP, 1978) and the idea of liminality (TURNER, 1974); b) learning in practice, legitimate peripheral participation and community of practice (LAVE; WENGER, 1991; LAVE, 2015); c) subjectivity and agency (ORTNER, 2006, 2007a, 2007b). The main conclusions of the research are I) that losing sight does not mean that the person becomes blind. It is not just a biological factor, it is a phenomenon crossed by the social and symbolic dynamics experienced by the subject; II) the learning of this movement does not happen within the programmatic-cognitive content of educational institutions; III) the idea of “acceptance” is insufficient to apprehend the movement between losing sight and “going on with life”, since the process presents itself in a socially and symbolically dense, dramatic path around the experience before and after the loss of visual acuity.